Isolation and Characterisation of Halogenated and Bioactive Compounds from Thalassospira sp. and Alteromonas sp. - Ali, Nadia Ghazi (UiT Norges arktiske universitet, 2019)
Bacterial natural products have contributed with a large part of the bioactive compounds that lead to drugs, and the biggest portion of the marketed antibiotics are bacterial products or their derivatives. Marine bacteria are not yet investigated to the same extend as their terrestrial counterparts. Therefore, they are considered a promising source for novel bioactive metabolites for drug development, which has been a trigger for the work carried out in this thesis. In this thesis, three Arctic marine bacteria of the genus Thalassospira, Alteromonas and Pseudomonas were investigated. The bacterial strains were cultivated, extracted and pre-fractionated. The fractions were screened for antibacterial and anticancer activity, and active fractions were re-fractionated. The bioactive re-fractionated extracts were dereplicated to investigate if the compounds suspected of being active, were novel or had been previously reported. Compounds assumed to be bioactive, as well as those with interesting chemical properties were isolated and characterised. One bioactive compound was isolated from the bacterial strain Thalassospira sp. The compound was active in both antibacterial and anticancer assays, and its structure remains to be elucidated. A di-halogenated compound was also isolated from this strain, it was however found to be chemically unstable. Moreover, three compounds were isolated from the bacterial strain Alteromonas sp. that remain to be structure elucidated and screened for bioactivity.